2017
DOI: 10.1038/s41598-017-11189-x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Oxygen Pulse Curve in Response to Incremental Exercise in Patients with Chronic Obstructive Pulmonary Disease – An Observational Study

Abstract: In COPD, pulmonary hyperinflation causes decreased stroke volume thereby decreased oxygen pulse (O2P). While O2P flattening is related to myocardial ischemia in cardiac patients, O2P patterns have seldom been explored in COPD. The aims of the study were to investigate O2P-curve patterns and associated factors in COPD. Seventy-five patients with stable COPD were enrolled. The demographics, cardiac size, physiological measurements and stress EKG were compared among O2P-curve pattern groups. An algorithm to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 39 publications
(42 reference statements)
1
17
0
Order By: Relevance
“…IC peak /TLC <23% has also been associated with lower O 2P and exercise capacity in patients with severe COPD [27]. Although OUES was not measured in this study, our previous study reported that IC peak /TLC was significantly correlated with O 2P and ∆O 2P (r = 0.35-0.36, both p < 0.05) [28]. These results support an interaction between hyperinflation and decreased cardiac function that can contribute to exercise limitation in these patients.…”
Section: The % Of Tlcmentioning
confidence: 54%
“…IC peak /TLC <23% has also been associated with lower O 2P and exercise capacity in patients with severe COPD [27]. Although OUES was not measured in this study, our previous study reported that IC peak /TLC was significantly correlated with O 2P and ∆O 2P (r = 0.35-0.36, both p < 0.05) [28]. These results support an interaction between hyperinflation and decreased cardiac function that can contribute to exercise limitation in these patients.…”
Section: The % Of Tlcmentioning
confidence: 54%
“…In addition, O 2 P curve pattern (O 2 PCP) is the trajectory of O 2 P during exercise, and therefore represents continuous monitoring of O 2 P. O 2 PCP is different in patients with obstructive airway disease and heart disease [ 7 ]. However, three types of O 2 PCP have been reported in patients with dyspnea [ 17 ] and COPD: plateau (P), decreasing (D), and increasing (I) types [ 18 ]. Furthermore, the P and D types are signs of cardiac dysfunction or myocardial ischemia in subjects with various heart diseases [ 17 , 19 , 20 ], and their presence should prompt additional cardiovascular work-up [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the P and D types are signs of cardiac dysfunction or myocardial ischemia in subjects with various heart diseases [ 17 , 19 , 20 ], and their presence should prompt additional cardiovascular work-up [ 19 , 20 ]. However, none of the O 2 PCP types are related to an ischemic heart in patients with COPD [ 18 ], and the relationships between O 2 PCP and ejection fraction in normal controls and in patients with COPD and chronic heart failure are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, heart rate % predicted and oxygen pulse at peak exercise were negatively correlated with V D /V Tpeak in the univariate and multivariate analyses (Table 3, r = À 0.46 and À0.63, P = .002 and <.0001, respectively; Table 2). Oxygen pulse at peak exercise [34] and its curve patterns [35] are influenced by both central cardiovascular function [36] and air trapping and dynamic hyperinflation in patients with chronic obstructive pulmonary disease. [34,35]…”
Section: Slow Vital Capacity and Heart Rate And Oxygen Pulse At Peak ...mentioning
confidence: 99%